2016
DOI: 10.1590/0102-3772e323220
|View full text |Cite
|
Sign up to set email alerts
|

Qualidades Psicométricas do Eating Attitudes Test (EAT-26) para Adolescentes Brasileiros do Sexo Masculino

Abstract: RESUMO A pesquisa objetivou avaliar as qualidades psicométricas do Eating Attitudes Test (EAT-26) para adolescentes brasileiros do sexo masculino. A amostra foi composta por 357 jovens, com idade entre 10 e 19 anos. Os resultados evidenciaram que 32,8% variância dos dados foram explicados por um único fator e o instrumento foi capaz de diferenciar seus escores em função do estado nutricional (p<0,05), além de correlacionar-se com as medidas de insatisfação corporal (rho=0,50). Confirmou sua consistência int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 20 publications
(50 reference statements)
1
23
0
10
Order By: Relevance
“…It should be noted that the present study was carried out away from the clinical environment, in adolescents who had not been diagnosed with ED; we found that 6.8% of our sample presented risk behaviors for developing ED. Similar percentages to those found in the present study were reported for Koreans, with 6.2% of adolescents presenting risk behaviors for developing ED [40]; higher percentages were reported for Peruvians, at 13.2% [55], Spanish adolescents, at 10.2% [51], and another study in Brazilians at 17.4% [34]. The risk of developing ED was significantly higher in girls than boys, corroborating previous findings [51].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It should be noted that the present study was carried out away from the clinical environment, in adolescents who had not been diagnosed with ED; we found that 6.8% of our sample presented risk behaviors for developing ED. Similar percentages to those found in the present study were reported for Koreans, with 6.2% of adolescents presenting risk behaviors for developing ED [40]; higher percentages were reported for Peruvians, at 13.2% [55], Spanish adolescents, at 10.2% [51], and another study in Brazilians at 17.4% [34]. The risk of developing ED was significantly higher in girls than boys, corroborating previous findings [51].…”
Section: Discussionsupporting
confidence: 91%
“…The Eating Attitudes Test (EAT-26) is a self-reporting questionnaire which analyzes unsuitable eating behaviors; it has been validated for Brazilians [33,34]. It contains 26 items with answers on a Likert-type scale (0 = never, hardly ever or occasionally; 1 = sometimes; 2 = often; 3 = always).…”
Section: Methodsmentioning
confidence: 99%
“…Para avaliar possíveis desvios comportamentais no padrão alimentar indicativos de transtornos alimentares, utilizou-se o EAT-26, desenvolvido por Garner et al 11 e traduzido e validado por Bighetti et al 12 e Fortes et al 13 . Esse instrumento contém 26 questões com respostas em escala do tipo Likert de seis pontos, sendo atribuídos pontos de 0 a 3 de acordo com as respostas marcadas: sempre (3 pontos), muitas vezes (2 pontos), às vezes (1 ponto), poucas vezes (0 ponto), quase nunca (0 ponto) e nunca (0 ponto).…”
Section: Métodosunclassified
“…Antes de cada aferição do peso, os entrevistadores taravam a balança, segundo recomendações do fabricante. O IMC foi calculado pelo produto da divisão do peso corporal pela altura ao quadrado (P/ A 2 ), ocorrendo classificação dos pesquisados em eutróficos (18,(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)9), sobrepeso (25,0-29,9) e obesidade (30,0-acima) 18 .…”
Section: Métodosunclassified
“…Escore maior ou igual a 20 representa indivíduos com riscos para transtorno alimentar (Garner et al, 1982). O EAT-26 foi validado no Brasil para adolescentes do sexo feminino (Bighetti, Santos, Santos & Ribeiro, 2004) e masculino (Fortes, Amaral, Conti, Cordás & Ferreira, 2016), apresentando alpha de Cronbach de 0,82 e 0,88, respectivamente. Para esta amostra, calculouse a consistência interna, identificando-se valores de 0,89 e 0,86 para meninas e meninos, respectivamente.…”
Section: Instrumentosunclassified